The effect of the first goal on match score in football for the home field advantage - Inan, T.; Cetin, B.; Gungorur, O. (Journal of Sport Pedagogy and Research, 2018)
The interest in sports in the world is increasing in parallel with the developments in communication technology, . As a result of this increase, the number of researches conducted on sports industry and sport management has also showed an increase. The field of sport that attracts the most attention worldwide is football. Data analysis and statistical research are also included in football researches in this field of sports that intertwines with different fields of science such as football management, finance and sports industry. In addition to the econometric measurement methods on the related researches, the variables affecting the results of the competition and the statistical analyzes that determine the impact strength of these variables are more abundant in the literature. As a result of the competitions, the variables affecting the results of a competition attract the attention of football players, technical team, fans, media organizations and sports managers. When it comes to this study, it was planned to statistically determine the effect of the first goal in the European football leagues on the results of the match. From 5 countries in Europe Spain, France, Germany, England and Italy in particular, data belonging to the matches of the teams in which they were the home team between 2014-2017 seasons was used. A total of 5478 matches were analyzed in which 1140 matches were from Spain, 918 from Germany, 1140 from France, 1140 from England and 1140 from Italy. The relationship between the first goal and the match result was determined by the chi-square independence test. SPSS 24.0 package program was used in the analysis. The first goal independent variable in the study was examined and it was found that there was a relationship between the first goal and the match results (p <0.05). As far as results of the research data are concerned, it was found that there was a relationship between the first goal scored and the match results of the 5 major European football leagues when the teams were the home teams during the three seasons. Accordingly, the importance of the first goal was demonstrated by this study.